Food business operator risk categorization. (20th October 2021) - Colarusso, G; Mazzone, P; Peirce, E; Pellicanò, R; Della Rotonda, M; Di Loria, G; Baldi, L; Mandato, D
Abstract: Issue: EU Reg 625/2017 establishes that all Food Business Operator FBO needs to be categorised based on risk. The risk rating is obtained by summing the scores of the non-conformities and risk factors checked. Description of the problem: In the past, various categorisation systems have been used but due to many FBO present in the regional territory, a new system of categorisation rapid and efficient is required. Results: The system classifies the risk of FBO in two phases: the first, based on static criteria (type and volume of production, market areas), in which a default category is established; the second, based on dynamic and technical criteria (provisions and scores of official control, structural and productive features), in which a definitive category is established. When a FBO is set up, it presents a declaration of start-up that included the static criteria: a preliminary risk category is determined. The authorities assign a definitive rating by a complex inspection, during which specific check-lists of the dynamic and technical criteria are completed. Each element is assigned a percentage weight, which contributes to the risk assessment, and so to the frequency of controls. A value >70% means high risk and 1 control per year; a value of 69.9-50% means medium risk and 1 control every 2 year; a value of 59.9-30% means low risk and 1 control every 3 years, and a value <29.9% indicates a negligible risk and controls on demand. In the period between 2 inspections, the score will be updated by the outcomes of any other official controls. The rating is updated according to favourable or unfavourable outcome. Lessons: In addition to being efficacious and efficient, this new system of categorisation optimises the work of the authorities. Key messages: This new categorisation system makes risk-based controls simpler and more efficacious. The project involves various Italian regions and the OECD, thereby enabling official controls to be standardised at the European level.